2000
DOI: 10.1054/bjoc.1999.1005
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with presumably hereditary uveal melanoma do not harbour germline mutations in the coding regions of either the P16INK4A, P14ARF or cdk4 genes

Abstract: SummaryIn familial cutaneous malignant melanoma (CMM), disruption of the retinoblastoma (pRB) pathway frequently occurs through inactivating mutations in the p16 (p16 INK4A /CDKN2A/MTS1) gene or activating mutations in the G1-specific cyclin dependent kinase 4 gene (CDK4). Uveal malignant melanoma (UMM) also occurs in a familial setting, or sometimes in association with familial or sporadic CMM. Molecular studies of sporadic UMM have revealed somatic deletions covering the INK4A-ARF locus (encoding P16 INK4A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…This is in keeping with observations by Singh et al, 7 but is lower than noted by Soufir et al, 42 who reported that 3.9% of patients had a family history of uveal melanoma. It is likely that these small differences reflect slight differences in ascertainment and the extent to which family histories were expanded.…”
Section: Discussionsupporting
confidence: 92%
“…This is in keeping with observations by Singh et al, 7 but is lower than noted by Soufir et al, 42 who reported that 3.9% of patients had a family history of uveal melanoma. It is likely that these small differences reflect slight differences in ascertainment and the extent to which family histories were expanded.…”
Section: Discussionsupporting
confidence: 92%
“…Deleterious germline mutations of CDKN2A have also not been found in previous studies of familial [11,12,14] and sporadic [8,13] ocular melanoma cases and ocular melanoma cases with a family history of cutaneous melanoma [11,14]. There is, however, some evidence that a loss of CDKN2A function may play a role in ocular melanoma.…”
Section: Discussionmentioning
confidence: 80%
“…The search for candidate susceptibility genes has focused on those known to be associated with cutaneous melanoma, e.g. the cell cycle regulatory genes, CDKN2A [7] and CDK4 [8], and the melanocortin 1 receptor gene (MC1R), a pigmentation-related gene [9,10], but no associations of germline mutations in these genes with ocular melanoma have been reported [8,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have found significant genetic (Naus et al, 2000;Soufir et al, 2000;Edmunds et al, 2002) and cytogenetic differences (Sisley et al, 2000) between the tumour types, despite both cells originating from the same cell type. Uveal melanoma is less studied in comparison to cutaneous melanoma, but to date no significant levels of mutated tumour-suppressor genes have so far been convincingly linked to it (Edmunds et al, 2002).…”
Section: Discussionmentioning
confidence: 91%